Mapping functional areas in Spain using mobile positioning data. (April 2022) - Rodríguez, M; Molina, J; Camacho, J A
To be effective, territorial development policies must rely on information collected at a proper spatial scale. This commentary compares functional and administrative geographies. We go beyond metropolitan areas and map functional areas across the entire national territory of Spain. These functional areas are delineated using commuting flows based on mobile positioning data. The results obtained revealed the existence of a substantial number of functional areas that do not belong to one sole region. This indicates that there is a discrepancy between the socioeconomic reality and the administrative areas employed for territorial development policy purposes. Functional areas could be particularly useful to address policy challenges in issues like labor market functioning, transport planning, housing, or public service provision.